Forest devolution and social capital: State-civil society relations in the Philippines - Magno, Francisco A. (Animo Repository, 2001)
Shifts in state-civil society relations have historically shaped forest devolution policies in the Philippines. Rules governing forest utilization and tenure emerge through competitive struggles as well as cooperative encounters involving state and civil society. Since the 1970s, the evolution of policy measures to transfer forest authority to local communities have contributed to the growth of reform advocates inside government and their strategic interactions with civil society organizations engaged in efforts to build equity and livelihood concerns into upland development programs. In examining the role of state-civil society interactions, one should understand how different stakeholders affect authority structures in the forest zones-the general pattern of distribution of power among the state and forest-dependent communities; the extent to which local communities, with the support of civil society organizations, are able to expand their opportunities to decide the fate of forests under contemporary laws and policies; the role of social capital as an institutional asset in improving local participation and capacity in forest governance.